KAJIAN KITAB TAISIRUL KHOLAQ: TROBOSAN PEMBELAJARAN AKHLAK METODE SALAFIYAH DI PONDOK PESANTREN - Sodikin, Ahmad (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
Morals are the spirit of Islam, where religion without morals is like a lifeless body. Morals are values that guarantee human salvation from the torment of hellfire. The position of morals in human life occupies an important place, as individuals as well as communities and nations, because the rise and fall of a society depends on its morals. Morals itself is an inseparable part of human life and is able to distinguish humans from other creatures. This research uses a descriptive approach where the data collected uses more words. The writing method used in this research is a qualitative method, this research aims to describe the learning of the book of Taisirul Khalaq in the formation of morals. The results of this study are expected to support the objectives of Islamic education itself, namely the realisation of perfect morals. In the process of collecting data, the author uses several methods, namely observation, interview and documentation methods